2012
DOI: 10.1016/j.febslet.2012.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional consequences of mutating a proteobacteria‐specific surface residue in the catalytic domain of Escherichia coli GluRS

Abstract: Edited by Michael IbbaKeywords: Glutamyl-tRNA synthetase tRNA Glu Glutamylation Proteobacteria Phylum-specificity Escherichia coli a b s t r a c t Nucleotides whose mutations seriously affect glutamylation efficiency are experimentally known for Escherichia coli tRNA Glu . However, not much is known about functional hotspots on the complementary enzyme, glutamyl-tRNA synthetase (GluRS). From structural and functional studies on an Arg266Leu mutant of E. coli GluRS, we demonstrate that Arg266 is essential for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…These GluRS sequences appear in the non-proteobacterial cluster, as sister clades of chlamydiae, fusobacteria and deinococcous-thermus. Unlike the canonical proteobacterial GluRS (the grey shaded region of Figure 2), GluRS belonging to the γ*-/α*-group seem to have appeared through some alternate evolutionary route, probably via HGT, as has been noted earlier [22]. Interestingly, in gatB phylogeny (Figure 3) the gatB sequences of the γ*-/α*-group are not outliers, indicating that only GluRS and not gatB appeared by HGT in these bacteria.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…These GluRS sequences appear in the non-proteobacterial cluster, as sister clades of chlamydiae, fusobacteria and deinococcous-thermus. Unlike the canonical proteobacterial GluRS (the grey shaded region of Figure 2), GluRS belonging to the γ*-/α*-group seem to have appeared through some alternate evolutionary route, probably via HGT, as has been noted earlier [22]. Interestingly, in gatB phylogeny (Figure 3) the gatB sequences of the γ*-/α*-group are not outliers, indicating that only GluRS and not gatB appeared by HGT in these bacteria.…”
Section: Resultsmentioning
confidence: 57%
“…Such phylum-specific trends have been observed experimentally for GluRS-tRNA Gln interaction – a D-GluRS-specific residue (Arg358) in Thermus thermophilus GluRS led to a relaxed tRNA Gln -discrimination [45] but when the same residue was mutated in H. pylori (GluRS1), no such effect was observed [46]. Similarly, for GluRS-tRNA Glu interaction, it was found that a proteobacteria-specific Arg residue (Arg 266 in E. coli GluRS) was absolutely essential for glutamylation efficiency of GluRS but the Arg is replaced by mostly Leu in non-proteobacterial GluRS [22]. …”
Section: Resultsmentioning
confidence: 99%
“…The diverse tRNA Glx specificities of bacterial GluRS call for structure-function correlation studies that will yield a clear understanding of the mechanisms that control the GluRS-tRNA Glx interaction in bacteria. Because the precise nature of the GluRS-tRNA Glx interaction in bacteria is phylum-specific (Dasgupta et al, 2012;Dasgupta & Basu, 2014), biochemical work performed on the GluRS-tRNA Glx interaction in a bacterium from one phylum may not be compatible with the GluRS structure from a bacterium belonging to a distant phylum.…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli is a model bacterium, some strains of which are pathogenic. Most biochemical studies have been performed on E. coli GluRS (Eco-GluRS), both in our laboratory (Dasgupta et al, 2009(Dasgupta et al, , 2012Saha et al, 2009Saha et al, , 2012 and in those of others (Sekine et al, 1996;Banerjee et al, 2004;Dubois et al, 2009). Recent reports have demonstrated how Eco-GluRS plays a role in pathogenesis by inducing multidrug tolerance upon binding to a eukaryote-like serine-threonine kinase (HipA; Germain et al, 2013;Kaspy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation